Development of a virtual patient record mobile app for pharmacy practice education - Terry Weiyi Toh; Wai Keung Chui; Kevin Yi-Lwern Yap (Archives of Global Professionals, 2014)
Introduction: Healthcare students are generally not exposed in the school curriculum to the workings of electronic health records (EHRs) and the types of patient health information (PHI) from EHRs that are relevant to clinical practices. A prototype virtual patient record (VPR) mobile app was created on two Samsung Galaxy Tab tablets to educate pharmacy students on the types of PHI available from EHRs. Materials and Methods: A pilot study was conducted from March-April 2013, whereby students used the app to solve counseling case scenarios. Respondents' demographics, mobile app usage patterns, perceptions regarding the app's usefulness, and its relevance as an EHR simulation tool, were determined through an online 14-item survey. Descriptive statistics, Chi-square tests, Fisher's exact tests and Mann-Whitney U tests were used to analyze the results. Results: Response rate was 100% (n = 31). Medical and healthcare apps were most commonly used (93.5%), and 67.7% of students used apps more than 5 times a day over the past 6 months. The app had 4 features ("PHR", "Case Questions", "Statutes" and "Useful Links"). Most students felt that the app features were understandable and self-explanatory (96.7%). Majority agreed that "PHR" (100%) and "Case Questions" (83.9%) were the most useful features. Majority (90.3%) found the app useful as a teaching aid. Conclusion: A VPR app has been successfully created and implemented as a teaching aid. Future development will involve migrating its features to the mobile web. Resources for health-related and medication-related information will be added. Furthermore, the app will be introduced to lower-year undergraduates before their hospital preceptorship attachments.